PSCPAC: Post-quantum secure certificateless public auditing scheme in cloud storage. (September 2021) - Li, Haifeng; Wang, Yuxin; Fu, Xingbing; Lan, Caihui; Wang, Caifen; Li, Fagen; Guo, He
Abstract: To reduce the local storage burden and enjoy the conveniently ubiquitous access, an increasing number of individuals and enterprises prefer to outsource their data to the cloud server. Due to the loss of physical control over data, how to guarantee the cloud server stores user's data honestly becomes an important security challenge. Meanwhile, most of existing public auditing schemes based on traditional public key cryptosystem either suffer from bearing the heavy burden of certificate management or possess an inherent key escrow drawback. Even worse, with the advent of powerful quantum computers, most of them could be cracked quickly by a large-scale quantum computer in polynomial time in the near future. To this end, we propose a novel post-quantum secure certificateless public auditing scheme in cloud storage (PSCPAC) from lattice assumptions. Compared with the existing schemes, our novel scheme enjoys the following promising merits: (1) removing the requirement for complicated certificate management in traditional PKI-based public auditing schemes; (2) eliminating the inherent key escrow problem in ID-based public auditing schemes; (3) providing resistance against quantum computers attacks. Correctness, security and performance analysis demonstrate that PSCPAC is provably secure, highly efficient and more practical for post-quantum security in cloud storage public auditing.